Analysis of the reference interest rates in Costa Rica, in national and foreign currency, from a financial investment perspective using the Fischer International Effect methodology - Arguedas Campos, Carlos Leonardo (2019)
The purpose of this article is to analyze, three indicators of the Central Bank of Costa Rica (BCCR): the basic passive rate (TBP), the exchange rate of the colon with respect to the US dollar (TC) and the effective rate in dollars (TED); as macroeconomic components that affect the valuation of an investment in colones or dollars. The study is carried out through the construction of an International Fischer Effect model (EFI), for the period between the first quarter of 2016 and the first quarter of 2019. Based on this model, it is evaluated, if during this period investing in dollars can generate a capital gain; in addition, the importance of absolute exchange rate changes to make such investments in dollars is outlined.